2003
DOI: 10.1046/j.1365-4362.2003.01891.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet's syndrome revisited: a review of disease concepts

Abstract: Sweet's syndrome, also referred to as acute febrile neutrophilic dermatosis, is characterized by a constellation of symptoms and findings: fever, neutrophilia, erythematous and tender skin lesions that typically show an upper dermal infiltrate of mature neutrophils, and prompt improvement of both symptoms and lesions after the initiation of treatment with systemic corticosteroids. Hundreds of patients with this dermatosis have been reported. The manifestations of Sweet's syndrome in these individuals have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
342
3
40

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(394 citation statements)
references
References 217 publications
(525 reference statements)
9
342
3
40
Order By: Relevance
“…5 Often, the syndrome may be preceded by an infection (of the upper respiratory tract, which is more common, or gastrointestinal tract) or even be associated with inflammatory bowel disease or pregnancy. 3,4,[6][7][8] An association between Sweet's Syndrome and the pathergy phenomenon -hypersensitivity of the skin more common in Behçet's disease and pyoderma gangrenosum -has also been described. 2.3 Extracutaneous manifestations include constitutional symptoms such as fever, malaise, diffuse pain, arthralgia, and myalgia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Often, the syndrome may be preceded by an infection (of the upper respiratory tract, which is more common, or gastrointestinal tract) or even be associated with inflammatory bowel disease or pregnancy. 3,4,[6][7][8] An association between Sweet's Syndrome and the pathergy phenomenon -hypersensitivity of the skin more common in Behçet's disease and pyoderma gangrenosum -has also been described. 2.3 Extracutaneous manifestations include constitutional symptoms such as fever, malaise, diffuse pain, arthralgia, and myalgia.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4,7 In cases associated with malignancy or drug-induced SS, treatment of the underlying disease and discontinuation of the drug, respectively, are associated with improvement of the condition. 2,3,7 Without treatment, SS lesions usually persist for several months, some, however, may have spontaneous resolution.The disease is characterized by frequent recurrences, which occur in both patients who have been treated and patients who had spontaneous remission. 2,3,7 In patients with SS associated with malignancy, relapses are more common and can be an early sign of recurrence of the underlying disease.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced SS is a well-recognized entity with granulocyte colony-stimulating factor most commonly responsible. 1 SS has not been associated with any of the medications taken by our patient and, although, case reports have associated SS with antiinflammatories (diclofenac and celecoxib). It seems unlikely that ibuprofen was causative, given the many years of prior exposure.…”
Section: Discussionmentioning
confidence: 47%
“…Involvement of ocular and oral mucosa, as in the present case, are well reported. 1 Other sites, which may be involved, include central nervous system, musculoskeletal system, kidneys, gastrointestinal tract, liver and lung. Laboratory abnormalities include neutrophilia and elevated erythrocyte sedimentation rate; however, large series have shown that in many cases these are normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation